Phase I Clinical Trial of Ifosfamide, Oxaliplatin, and Etoposide (IOE) in Pediatric Patients With Refractory Solid Tumors. Issue 1 (January 2015) - Lam, Catherine G.; Furman, Wayne L.; Wang, Chong; Spunt, Sheri L.; Wu, Jianrong; Ivy, Percy; Santana, Victor M.; McGregor, Lisa M.
<x xml:space="preserve">Abstract</x> Oxaliplatin, although related to cisplatin and carboplatin, has a more favorable toxicity profile and may offer advantages in combination regimens. We combined oxaliplatin, ifosfamide, and etoposide (IOE) and estimated the regimen's maximum tolerated dose (MTD) in children with refractory solid tumors. Dose-limiting toxicity (DLT) and MTD were assessed at 3 dose levels in a 21-day regimen: day 1, oxaliplatin 130 mg/m2 (consistent dose); days 1 to 3, ifosfamide 1200 mg/m2/d (level 0) or 1500 mg/m2/d (levels 1 and 2) and etoposide 75 mg/m2/d (levels 0 and 1) or 100 mg/m2/d (level 2). Course 1 filgrastim/pegfilgrastim was permitted after initial DLT determination, if neutropenia was dose limiting. Seventeen patients received 59 courses. Without filgrastim (n=9), DLT was neutropenia in 2 patients at dose level 1. No DLT was observed after adding filgrastim (n=8). There was no ototoxicity, nephrotoxicity >grade 1, or neurotoxicity >grade 2. One patient experienced a partial response and 9 had stable disease after 2 courses. In conclusion, the IOE regimen was well tolerated. Without filgrastim, neutropenia was dose limiting with MTD at ifosfamide 1200 mg/m2/d and etoposide 75 mg/m2/d. The MTD with filgrastim was not defined due to early study closure. Filgrastim allowed ifosfamide and etoposide dose escalation and should be included in future studies.